The value of plasma D-dimer level on admission in predicting no-reflow after primary percutaneous coronary intervention and long-term prognosis in patients with acute ST segment elevation myocardial infarction - TİGEN, MUSTAFA KÜRŞAT (SPRINGER, 2014)
D-dimer is a final product of fibrin degradation and gives an indirect estimation of the thrombotic burden. We aimed to investigate the value of plasma D-dimer levels on admission in predicting no-reflow after primary percutaneous coronary intervention (p-PCI) and long-term prognosis in patients with ST segment elevation myocardial infarction (STEMI). We retrospectively involved 569 patients treated with p-PCI for acute STEMIs. We prospectively followed up the patients for a median duration of 38 months. Angiographic no-reflow was defined as postprocedural thrombolysis in myocardial infarction (TIMI) flow grade < 3 or TIMI 3 with a myocardial blush grade < 2. Electrocardiographic no-reflow was defined as ST-segment resolution < 70 %. The primary clinical end points were mortality and major adverse cardiovascular events (MACE). The incidences of angiographic and electrocardiographic no-reflow were 31 and 39 % respectively. At multivariable analysis, D-dimer was found to be an independent predictor of both angiographic (p < 0.001), and electrocardiographic (p < 0.001) no-reflow. Both mortality (from Q1 to Q4, 5.7, 6.4, 11.3 and 34.1 %, respectively, p < 0.001) and MACE (from Q1 to Q4, 17.9, 29.3, 36.9 and 52.2 %, respectively, p < 0.001) rates at long-term follow-up were highest in patients with admission D-dimer levels in the highest quartile (Q4), compared to the rates in other quartiles. However, Cox proportional hazard model revealed that high D-dimer on admission (Q4) was not an independent predictor of mortality or MACE. In contrast, electrocardiographic no-reflow was independently predictive of both mortality [Hazard ratio (HR) 2.88, 95 % confidence interval (CI) 1.04-8.58, p = 0.041] and MACE [HR 1.90, 95 % CI 1.32-4.71, p = 0.042]. In conclusion, plasma D-dimer level on admission independently predicts no-reflow after p-PCI. However, D-dimer has no independent prognostic value in patients with STEMI.
Keywords: D-dimer; No-reflow; Primary angioplasty; Myocardial infarction; Prognosis; PRIMARY ANGIOPLASTY; DISTAL EMBOLIZATION; CHEST-PAIN; REPERFUSION; THERAPY; PREVENTION; FEATURES; TRIALS